Clinical Practice Guidelines for Valvular Prostheses Dysfunction Treatment - Lázaro De la Cruz Avilés; Félix Rene Jorrín Román; Ernesto Falcón Pérez (Medisur)
Clinical Practice Guidelines for Valve Prostheses Dysfunction Treatment. The introduction of an artificial valve allows improving life quality and expectancy of an important number of patients and can be considered a common treatment within advanced heart valve disease. However, persons with this kind of prosthesis usually present another disease caused by the potential complications associated with the uses of anti-clotting medications. This document includes the different classifications of artificial heart valves and different kinds of dysfunctions, and updates those aspects related with treatment stressing the appropriate behaviour when valve or prosthesis thrombosis occurs. It includes assessment guidelines focused on the most important aspects to be accomplished.